Radiopaque Strontium Fluoroapatite Glass-Ceramics - Höland, Wolfram; Schweiger, Marcel; Dittmer, Marc; Ritzberger, Christian (Frontiers in Bioengineering and Biotechnology, 2015)
The controlled precipitation of strontium fluoroapatite crystals, was studied in four base glass compositions derived from the SiO2 – Al2O3 – Y2O3 – SrO – Na2O – K2O/Rb2O/Cs2O – P2O5 – F system. The crystal phase formation of these glasses and the main properties of the glass-ceramics, such as thermal and optical properties and radiopacity were compared with a fifth, a reference glass-ceramic. The reference glass-ceramic was characterized as Ca-fluoroapatite glass-ceramic. The four strontium fluoroapatite glass-ceramics showed the following crystal phases: a) Sr5(PO4)3F – leucite, KAlSi2O6 , b) Sr5(PO4)3F – leucite, KAlSi2O6, and nano-sized NaSrPO4 c) Sr5(PO4)3F – pollucite, CsAlSiO4 , and nano-sized NaSrPO4, d) Sr5(PO4)3F – Rb-leucite, RbAlSi2O6, and nano-sized NaSrPO4. The proof of crystal phase formation was possible by X-ray diffraction (XRD). The microstructures, which were studied using scanning electron microscopy (SEM) demonstrated a uniform distribution of the crystals in the glass matrix. The Sr-fluoroapatites were precipitated based on an internal crystallization process, and the crystals demonstrated a needlelike morphology. The study of the crystal growth of needlelike Sr-fluoroapatites gave a clear evidence of an Ostwald ripening mechanism. The formation of leucite, pollucite and Rb-leucite was based on a surface crystallization mechanism. Therefore, a twofold crystallization mechanism was successfully applied to develop these types of glass-ceramics. The main focus of this study was the controlled development of glass-ceramics exhibiting high radiopacity in comparison to the reference glass-ceramic. This goal could be achieved with all four glass-ceramics with the preferred development of the Sr-fluoroapatite – pollucite-type glass-ceramic. In addition to this main development, it was possible to control the thermal properties. Especially the Rb-leucite containing glass-ceramic showed the highest coefficient of thermal expansion (CTE). These glass-ceramics allow optical properties, especially the translucency and color, to be tailored to the needs of biomaterials for dental applications. The authors conclude that it is possible to use twofold crystallization processes to develop glass-ceramic biomaterials featuring different properties, such as specific radiopacity values, CTEs and optical characteristics.